A Study of CO Emission Sources and Their Impacts on the Respiratory Systems of Patients in Al-Muthanna Governorate - Ali, Farah; Ali Abdulhamza Al -Fanharawi (University of Thi-Qar Journal of Science, 2025)
This study examines carbon monoxide (CO) emissions and their health effects on individuals with respiratory conditions such as asthma, COPD, and bronchitis. CO sources include biomass burning, industrial processes, and vehicle exhaust, with CO's high hemoglobin affinity impairing oxygen transport. The current study aimed to assess CO emissions' impact on respiratory health in Al-Muthanna Governorate. From November 2023 to July 2024, CO levels were measured in high-emission areas, including a cement factory, oil refineries, and seven fuel stations, using Drager X am 5000 devices. Two control areas, Hay Al Hussein and Al Doha Residential Compound, were used for comparison.The study involved 120 participants: 60 fuel station workers, 20 refinery residents, and 40 controls. The highest CO concentration was from the cement plant (48.98 ppm), with the lowest 100 meters from station S5 (1.67 ppm). Control areas had no detectable CO (0.00 ppm). Health assessments included blood (WBC, Lym, Neu, Eos), lung function (FVC, FEV, PEF), and immunological markers (IgE).  Findings showed high CO levels near sources, exceeding global limits. Affected individuals aged 30–50 had increased eosinophils (7.60–9.90%), reduced lung function (FVC 54–81%, FEV 27.33–49.75%, PEF 16–26.75%), and elevated IgE (170.5–518.3 U/mL), with bronchial allergies more common than asthma.